Economical Systematic Approach For On-Board Processing And Control, In Remote Sensing Equipment (Journal of Pharmaceutical Negative Results, 2023)
In the development of equipment to be used in the remote sensing environment, it is recommended to consider in the design certain technical aspects such as: energy consumption, device size, performance, computational capacity, connectivity, radiation tolerance, among others. Therefore, certain electronic components capable of providing these characteristics are used, which makes their cost high and it becomes difficult to acquire these electronic components for special use. The proposal presented in this investigation, is the use of the embedded card Tegra TK1 of the NVIDIA brand, to be used as a base device for remote sensing equipment. This card provides considerable computational capacity. This card is composed of a CPU and the GPU, as well as communication buses and the communication card expansion to connect certain devices such as sensors and actuators. Another feature is fault tolerance and critical execution times that are critical in these types of equipment, among the main tasks, are the sending of telemetry, control of navigation devices, and synchronization among other tasks that will depend on the payload of the equipment. As a result, it is proposed to install a real-time operating system on the TK1 card, which ensures that the tasks are fulfilled in the established times and with the criticality that is required.